Meningkatkan Kemampuan Mengenal Lambang Bilangan 1 sampai 5 melalui Media Busy Book bagi Anak Tunagrahita Ringan - Hartati, Peby Tri; Ardisal, Ardisal (Jurnal Penelitian Pendidikan Khusus, 2021)
This study aims to prove whether the busy book media can improve the ability to recognize the symbols numbers 1 to 5 in children with mild mental retardation. This research uses experimental research in the form of Single Subject Research (SSR) with A-B-A design. The data analysis technique used visual graph analysis. The results of data analysis from 17 observations in 3 conditions, namely at baseline (A1) obtained results of 0%, 0%, 0%. Intervention (B) obtained results of 20%, 20%, 40%, 60%, 40%, 60%, 60%, 60%. Finally, at baseline (A2) the results were 40%, 60%, 80%, 60 %, 60%, 60%. The results showed that the ability to recognize the symbols of numbers 1 to 5 increased after using busy book media for mild mentally retarded children class I / C at SLBN 1 Painan.